THE APPLICATION OF E-TOURISM IN SMALL AND MEDIUM-SCALE TOURISM IN INDONESIA: A STRATEGIC MANAGEMENT VIEW - Ananda Sabil Hussein; Untoro Widagdo; Yeni Asriwulan (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
Tourism sector is one of state’s income that cannot be separated from the roles of small and medium scale business unit. In accordance with the development of science and technology, tourism sector cannot be separated with the application of information technology commonly called as E-Tourism. In general, E-Tourism is an application of information technology in the field of tourism in order to achieve effectiveness and efficiency in promoting the tourism sectors in Indonesia. Its application in tourism sector can be used as a medium to promote virtual promotion in order to get wider markets. It is also known that most of the tourists who come to Indonesia are from developed countries and they are familiar with the application of ICT. By applying E-Tourism tourists andprospective ones are able to access tourism information fast and accurately. It is beneficial for small and medium-scale businessmen. The article attempts to give a description about the effects of E-Tourism on small and medium-scale business unit in Indonesia. It is expected that those involved in tourism business are able to formulate a strategicmarketing that can provide competitive advantages, while for researchers it is hoped that the article will be beneficial for future research related to E-Tourism .Keywords: Tourism, small and medium scale business unit, E-Tourism, ICT, Strategicmarketing